Use of computed tomography to compare two femoral head and neck excision ostectomy techniques as performed by two novice veterinarians - O’Donnell, M. D.; Warnock, J. J.; Bobe, G.; Scholz, R. P.; Wiest, J. E.; Nemanic, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objectives: To compare the results of femoral head and neck excision (FHNE) ostectomy performed by two novice veterinarians using an osteotome and mallet or microsagittal saw.Methods: In this ex vivo cadaveric study, hindlimbs of eight canine cadavers were randomized to FHNE with osteotome or micro sagittal saw as performed by two recently graduated veterinarians. The hindimbs were imaged by computed tomography (CT) before and after the osteotomy. Post FHNE CT images were evaluated by a board certified radiologist blinded to the ostectomy technique for assessment of the number of bone fragments, fissures, smoothness of osteotomy margination, and volume of residual fe-moral neck.Results: Femoral head and neck excision performed with the osteotome produced more peri-ostectomy bone fragments, cortical fissures, irregular margins, and residual femoral neck volume, compared with osteotomy using a saw.Clinical relevance: Compared to FHNE performed with a sagittal saw, osteotome FHNE resulted in a greater bone trauma and residual neck bone volume, which would require post-ostectomy modification in a clinical setting.
Keywords: Computed tomography; femoral head and neck excision; coxofemoral joint; osteotome; sagittal saw